Content Analysis of Persian Language and Writing Textbooks in Elementary School from the Perspective of Attention to the Six Educational Domains - Marzban Adibmanesh; Mohammad Reza Pashaei (پژوهش در آموزش معارف و تربیت اسلامی)
The objective of this study is to analyze the content of Persian language and writing textbooks for elementary school in terms of attention to the six educational domains. The research method is descriptive, using content analysis based on Shannon entropy. The study population included Persian and writing textbooks for elementary school during the 2024-2025 academic year. Data were analyzed and described using the analytical approach. Results show that among the six grades of Persian textbooks, the highest attention to the dimensions and components of the six educational domains outlined in the Fundamental Transformation Document of Education was observed in the fifth-grade Persian textbook (19.40%), while the second-grade textbook showed the least attention (11.85%). Regarding the dimensions of the textbooks, the faith-based, devotional, and moral domain received the most attention (29.18%), followed by the physical-biological domain (22.35%), with the economic and vocational domain receiving the least (8.50%). For the writing textbooks, the sixth-grade writing textbook received the most attention to the six educational domains (18.80%), while the second-grade writing textbook received the least (15.50%). Among these, the faith-based and devotional domain was emphasized most (28.80%), while the economic and vocational domain received the least attention (11.37%). Overall, both textbook types showed the greatest focus on the faith-based and devotional domain, and the least on the economic and vocational domain.